DISEASE ACTIVITY, STERIOD-FREE REMISSION, AND CLINICAL OUTCOME ASSESSMENTS OF PEDIATRIC ULCERATIVE COLITIS AND CROHN'S DISEASE PATIENTS RECEIVING BIOLOGIC THERAPY. (21st January 2021) - Hunter, Theresa; Komocsar, Wendy; Liu, Chunyan; Colletti, Richard; Steiner, Steven; Dotson, Jennifer; Benkov, Keith; Zhang, Nanhua; Crandall, Wallace
Abstract: Objectives: To assess disease activity, steroid-free remission, and clinical outcome assessments among pediatric UC and CD patients who initiated a biologic after being enrolled in the ICN registry. Methods: Pediatric patients who were diagnosed with UC or CD between June 1, 2013-Dec 31, 2019, who, after enrollment in the ICN registry, initiated a biologic and were actively followed for at least 12 months after first maintenance dose were included in this study. Descriptive statistics of baseline patient demographics were summarized for the overall IBD patient population and separately for UC and CD. PUCAI, partial Mayo score, and PGA were assessed in UC patients; and the sPCDAI and PGA were assessed in CD patients at first maintenance dose, 1-year and 3-year time points. Kappa coefficients were used to assess the level of agreement between the PUCAI, Mayo clinical score, and PGA for UC patients and the level of agreement between the sPCDAI and PGA for CD patients at different time points. Results: A total of 1, 887 pediatric IBD patients (UC=350; CD=1, 537) were included in this study. Patients had a mean age at diagnosis of 12.9 years, 57.1% were male, and 80.6% were White. Mean PUCAI scores of UC patients decreased from 12.1 at first maintenance dose, to 5.7 at 1-year, and 3.7 at 3-years; the proportion of UC patients in steroid-free remission by PUCAI increased from 46.2% at first maintenance dose, to 75.0% at 1 year and 80.4% at 3 years. The proportion of UC patients that were quiescent based on PGA also increased from 67.2% at first maintenance dose, to 84.2% at 1-year and 92.6% at 3-years. The proportion of UC patients that were in remission based on Partial Mayo score also increased from 72.1% at first maintenance dose, to 87.5% at 1-year and 92.3% at 3-years. Mean sPCDAI score of CD patients decreased from 9.5 at first maintenance dose, to 6.7 at 1-year, and 6.3 at 3-years; the proportion of CD patients in steroid-free remission by sPCDAI increased from 63.8% at first maintenance dose, to 81.2% at 1-year and 85.4% at 3-years. The proportion of CD patients who were quiescent based on PGA also increased from 69.2% at first maintenance dose, to 85.3% at 1-year and 89.6% at 3-years. In UC patients, the kappa coefficients between PUCAI and PGA ranged from 0.46–0.66, PUCAI and partial Mayo ranged from 0.52–0.72, and PGA and Partial Mayo score ranged from 0.73–1.00 at different time points. For CD patients, the kappa coefficient between sPCDAI and PGA ranged from 0.40–0.48 at different time points. Conclusion: This study found that disease activity scores improved over time, with more pediatric UC and CD patients achieving steroid-free remission 1-year and 3-years after first biologic maintenance dose. There was modest correlation between disease activity assessments, with the correlation between the PGA and Partial Mayo score being the strongest.